FOLK PERCEPTIONS OF THE SYMBOL OF HAIR IN THE TRADITIONAL LIFESTYLE OF UZBEKS - Sh. Kh. Rakhimova (Modern American Journals, 2026)
This article explores the beliefs associated with the symbol of hair in the spiritual culture of the Uzbeks of the Fergana Valley. Particular attention is given to the historical roots of hair-related perceptions and to how this symbol is reflected in rituals connected with childbirth, child upbringing, marriage, and mourning ceremonies. The study analyzes the cultural and symbolic meanings attributed to hair within traditional practices and worldview patterns of the local population.
Keywords: Fergana Valley, Uzbeks, symbol of hair, ritual, childbirth, marriage ceremonies, mourning rituals, custom, tradition, ethnos.